Do Inflation and Exchange Rates Predict Sectoral Equity Returns? Evidence from Banking (Interest-Sensitive) and Healthcare (Non-Interest-Sensitive) Sectors in Pakistan (2013–2023): A Segmented Market Performance Analysis - Malik, Dr Mehwish; Sarwar, Dr. Bilal; Shahzad, Dr. Imran (Minhaj International Journal of Economics and Organization Sciences, 2025)
This study explores the predictive impact of two significant macroeconomic indicators; (inflation and exchange rate) on sectoral returns on equity in Pakistan, focusing on interest-sensitive (banking) and non-interest-sensitive (healthcare) sectors. Due to the sharp economic instability in emerging markets economies (EMEs), the research utilizes analytical tools, a quantitative time series approach using monthly data from 2013 to 2023. The methodology combines unit root testing, descriptive statistics, correlation analysis, and out-of-sample forecasting to investigate the stationarity and predictive dynamics of the variables. The results show that inflation has a statistically substantial and adverse effect on stock returns and banks in the healthcare sector, with stronger effects detected in the interest-sensitive sector. In contrast, exchange rate depreciation is originating to have a positive and significant influence on equity returns, predominantly in the healthcare sector after the analysis of healthcare markets, signifying sectoral resilience to currency fluctuations. The results support the notion that inflation and exchange rates have meaningful predictive power over sectoral performance, highlighting their role in determining investment strategies and macroeconomic policy. The study relates to the limited body of literature on sector-specific financial forecasting and simulation in emerging market economies (EMEs) and provides valuable understandings for policymakers to develop well-structured government policies and regulations. It also provides the essential information for investors seeking to mitigate risk and improve portfolio performance among macroeconomic volatilities and uncertainty.